Comparison of Holmium Laser and Pneumatic Lithotripsy in Treatment of Ureteral Stones - Bhandari, Bharat Bahadur; Basnet, RB (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: To compare the effectiveness and complications of treatment of ureteric stones by holmium laser lithotripsy and pneumatic lithotripsy. Methods: Comparison of 100 patients with ureteric stones, 50 of whom were treated with pneumatic lithotripsy and 50 with holmium laser lithotripsy was done and effectiveness and complications of the two were analysed. Results: Both the groups were similar in respect to sex, age, stone size and location of the stones. Successful stone fragmentation occurred in 94 % on pneumatic group and in 92 % on laser group. On following the patients for a month, stone free rate was 98 % in both the groups. None of the patients had any complications relating to the procedures. Conclusion: Although pneumatic lithotripsy has more retrograde migration of ureteric stones, the results are comparable to holmium laser. Other complications are very rare